Racial and ethnic differences in severity of coronary calcification among patients undergoing PCI: Results from a single-center multiethnic PCI registry. (October 2021) - Bienstock, Solomon W.; Samtani, Rajeev; Lai, Ashton C.; Baber, Usman; Sperling, Dylan; Camaj, Anton; Feinman, Jason; Ting, Peter; Kocovic, Nikola; Li, Emily; Goldman, Martin E.
Abstract: Background: Although population-based studies have demonstrated racial heterogeneity in coronary artery calcium (CAC) burden, the degree to which such associations extend to percutaneous coronary intervention (PCI) cohorts remains poorly characterized. We sought to evaluate the associations between race/ethnicity and CAC in a PCI population. Methods: This single center retrospective study analyzed 1025 patients with prior CAC who underwent PCI between January 1, 2012 and May 15, 2020. Patients were grouped as non-Hispanic White (NHW, N = 779), non-Hispanic Black (NHB, N = 81) and Hispanic (H, N = 165). Associations between race and CAC (Agatston units) were examined using negative binomial regression while adjusting for baseline parameters. Results: Among the 1025 patients (mean age 65.8, 70% male) who underwent PCI, NHW, NHB, and H populations had median CAC scores of 760, 500, and 462 Agatston units, respectively (p < 0.0001). Hispanic patients displayed a higher burden of diabetes mellitus, hypertension and hyperlipidemia compared with other groups. After adjusting for baseline differences and compared with NHW, the inverse association between Hispanic and CAC persisted (β = -324.1, p < 0.0001) whereas differences were not significant for NHB (β = -51.5, p = 0.67). Conclusions: Despite a higher risk clinical phenotype, Hispanic patients who underwent PCI had significantly lower CAC compared with non-Hispanic patients. Thus, current risk stratification models using universalized CAC scores may underestimate the risk for the Hispanic population. Race/ethnicity-informed CAC thresholds may better guide clinical decisions.